Scaling up agricultural innovation for inclusive livelihood and productivity outcomes in sub-Saharan Africa: The case of Nigeria - Ogunniyi, Adebayo; Oluseyi, Olagunju Kehinde; Adeyemi, Ogundipe; Kabir, Salman K.; Phillips, Francis (Wiley, 2017)
Agricultural research programmes driven by agricultural innovation system concepts usually aim to change the way in which low income rural agrarian households in a nation like Nigeria communicate with the market and the decision‐making strategies pertaining to development of their agri‐business and the scarce resources which are at their disposal. We assess the extent to which the use of these innovative agricultural research interventions impact upon the livelihood and productivity outcomes of rural smallholder farmers in sub‐Saharan African using a case study of Nigeria. Using propensity score matching as a means of establishing a valid counterfactual and single differencing to measure impact, the study establishes that rural incomes and output are significantly impacted by agricultural research interventions that are driven by agricultural innovation systems concepts. The study finds that participating households had better livelihood, productivity and more diversified income portfolios during the implementation of innovative research intervention as a result of greater linkages to markets and capacity building opportunities; phasing out of the research programme reduced the diversity of income portfolios and led to the erosion of livelihoods. Therefore, agricultural innovation system concepts should be mainstreamed in all public agricultural extension and research programmes.